2005
DOI: 10.1097/01.ogx.0000172313.32069.ea
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome of Lupus Pregnancy: A Prospective Study of 29 Pregnancies

Abstract: Maternal thrombophilia is an accepted risk factor for perinatal death, having been associated with pregnancy-related thrombosis and preeclampsia, intrauterine growth restriction, placental abruption, recurrent miscarriage, and late fetal loss. Up to two thirds of these vascular complications can be related to some form of inherited or acquired thrombophilia. It is not clear whether paternal factors contribute to thrombophilia-related perinatal mortality. The investigators examined data from a prospective regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 0 publications
1
31
1
1
Order By: Relevance
“…Most studies have shown that lupus tends to flare during pregnancy and after pregnancy; in some patients flares were mild such as arthritis, constitutional and cutaneous manifestations, and in others they were more serious problems affecting the kidneys and central nervous system. 6,9,17,34 Lupus flare in pregnancy was found to be related to adverse pregnancy outcomes including pregnancy loss, preterm delivery and IUGR in our patients, consistent with previous reports. 8 This was the strongest predictor of all the adverse pregnancy outcomes among the characteristics we compared.…”
Section: Discussionsupporting
confidence: 94%
“…Most studies have shown that lupus tends to flare during pregnancy and after pregnancy; in some patients flares were mild such as arthritis, constitutional and cutaneous manifestations, and in others they were more serious problems affecting the kidneys and central nervous system. 6,9,17,34 Lupus flare in pregnancy was found to be related to adverse pregnancy outcomes including pregnancy loss, preterm delivery and IUGR in our patients, consistent with previous reports. 8 This was the strongest predictor of all the adverse pregnancy outcomes among the characteristics we compared.…”
Section: Discussionsupporting
confidence: 94%
“…While we cannot document these two cases as "complement remission", more clinical practices and long-term follow-up for the other 9 cases are necessary, to see whether autologous hematopoietic stem cell transplantation can lead to SLE remission for a long-term duration or even cure the disease completely. It should be acknowledged that SLE is a multifactor autoimmune disease processes with polygenic susceptibility background [14] being modulated by environmental factors such as estrogen levels [7,[14][15][16], which might all aVect the whole strategy and outcome of autologous hematopoietic stem cell transplantation. This also could explain why some SLE cases relapse following transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…SLE disease activity may become severe at postpartum period [7]. Maternal risks have been more diYcult to evaluate because of the unpredictable nature of the disease and limited individual experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), à la présence des autoanticorps et à la toxicité éventuelle des traitements proposés [41]. [42,43]. Les études in vitro évoquent une toxicité directe des antiphospholipides sur le développement embryonnaire et trophoblastique, avec des défauts d'invasion expliquant les FCS pré-coces et les pathologies placentaires plus tardives [44].…”
Section: Hypothèses Physiopathologiquesunclassified